Breast feeding increases concentrations of IgA in infants' urine. Issue 8 (August 1987) - Prentice, A
Abstract : To investigate the influence of breast feeding on mucosal immunity the concentrations and daily outputs of IgA and lactoferrin in urine were measured in 10 breast fed and 12 infants fed on formula milk at 6 and 12 weeks of age. The concentrations and outputs of secretory IgA in urine were significantly higher in the breast fed group by a factor of three. The secretion of IgA in urine by the breast fed infants was characteristic of the baby and was not related to the intake of IgA from breast milk. Lactoferrin concentrations were similar in the two groups at both ages. In addition to secretory IgA, two thirds of all samples contained proteins with alpha chain but no secretory component antigenic determinants. Breast feeding seems to increase the local production of secretory IgA into the urinary tract during early childhood, thus providing enhanced protection from infection.